2006
DOI: 10.1016/j.trstmh.2005.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antibody response to Anopheles salivary antigens as a potential marker of risk of malaria

Abstract: The evaluation of human immune responses to arthropod bites may be a useful marker of exposure to vector-borne diseases, with applications to malaria, the most serious parasitic infection in humans. The specific antibody (Ab) IgG response to saliva obtained from Anopheles gambiae mosquitoes was evaluated in young children from an area of seasonal malaria transmission in Senegal. Specific IgG was higher in children who developed clinical Plasmodium falciparum malaria within the 3 months that followed than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
153
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(174 citation statements)
references
References 19 publications
13
153
0
8
Order By: Relevance
“…This was not entirely unexpected, because SGSs are large proteins sharing little homology with any vertebrate protein, and thus, relatively high antibody titers would be expected from a small antigen dose. High immunogenicity opens the possibility that human anti-SGS antibodies could serve as sensitive markers for assessing exposure of humans to mosquito bites (3,7) and that this could be an important tool in areas of low to moderate mosquito density. Furthermore, because the large N-terminal region of the SGSs is highly variable, small recombinant SGS peptides could be used as species-specific and genus-specific antigens in this epidemiological strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was not entirely unexpected, because SGSs are large proteins sharing little homology with any vertebrate protein, and thus, relatively high antibody titers would be expected from a small antigen dose. High immunogenicity opens the possibility that human anti-SGS antibodies could serve as sensitive markers for assessing exposure of humans to mosquito bites (3,7) and that this could be an important tool in areas of low to moderate mosquito density. Furthermore, because the large N-terminal region of the SGSs is highly variable, small recombinant SGS peptides could be used as species-specific and genus-specific antigens in this epidemiological strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most practical use for mosquito saliva is as a tool for surveying human exposure to mosquito bites (3). A large percentage of the world's population lives in areas where the rate of mosquito-borne disease transmission is not accurately reflected by standard entomological measures of mosquito activity (5,6).…”
mentioning
confidence: 99%
“…An ELISA technique was carried out using WSE from uninfected mixed male and female G. fuscipes fuscipes, and sera were tested for IgG Ab as previously described for Anopheles. 9 Maxisorp plates (Nunc, Roskilde, Denmark) were coated with mixed WSE (2 g/mL) in carbonate/bicarbonate buffer and saturated with blocking buffer (Pierce). Individual sera were incubated (1:120) in phosphate-buffered saline (PBS)-Tween 1%, and IgG detection was performed using a mouse anti-human IgG biotinylated mAb (BD Pharmingen, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Studies on different vectors (Triatoma, Aedes, Phlebotomus, Anopheles) have suggested that the evaluation of human specific Ab response to saliva and/or to recombinant salivary protein could evaluate the exposure of individuals to vector bites and thus could be an indicator of risk to pathogens transmission. [6][7][8][9] Few studies have explored the immune properties of Glossina saliva. 10 Previous study indicated that IgG response to Glossina morsitans morsitans saliva and to specific salivary Tsal proteins were detected in exposed and infected Ugandan populations.…”
Section: Introductionmentioning
confidence: 99%
“…As anti-sandfly saliva antibodies are a good marker of exposure to sandfly bites, their possible use as a marker of risk of Leishmania transmission was tested. In an analogous setting, anti-vector saliva antibody response was suggested as a marker of risk of malaria or Lyme disease transmission (Remoue et al, 2006;Schwartz et al, 1991). However, in humans from endemic area for visceral leishmaniasis in Brazil, the presence of antibodies against Lu.…”
Section: Antibodies Against Sandfly Saliva: Marker Of Exposure To Sanmentioning
confidence: 99%